Evaluasi Pemilihan Kepala Desa Berbasis Elektronik dalam Rangka Pelayanan Publik di Kabupaten Gresik - Asroin Widyana* (Airlangga Development Journal, 2017)
The village has its original autonomy (geruine autonomy) emerging and its existence is not due to the delegation or the authority of the higher units of government, but is sourced and rooted in the original rights of the village concerned. The original rights are sourced from the rights of origin, customs and traditional rights of the village concerned. Village autonomy can be said to be an autonomy sourced from cultural wisdom, customs and common sense of the village. According to regulation of the Minister of Villages, Customs and common sense of the village.